From Augmented to Virtual Reality in Plastic Surgery: Blazing the Trail to a New Frontier - Sullivan, Janessa; Skladman, Rachel; Varagur, Kaamya; Tenenbaum, Elijah; Sacks, Jacob L.; Martin, Cameron; Gordon, Terry; Murphy, John; Moritz, William R.; Sacks, Justin M. (Journal of Reconstructive Microsurgery, 2023)
Background Augmented reality (AR) and virtual reality (VR)—termed mixed reality—have shown promise in the care of operative patients. Currently, AR and VR have well-known applications for craniofacial surgery, specifically in preoperative planning. However, the application of AR/VR technology to other reconstructive challenges has not been widely adopted. Thus, the purpose of this investigation is to outline the current applications of AR and VR in the operative setting.Methods The literature pertaining to the use of AR/VR technology in the operative setting was examined. Emphasis was placed on the use of mixed reality technology in surgical subspecialities, including plastic surgery, oral and maxillofacial surgery, colorectal surgery, neurosurgery, otolaryngology, neurosurgery, and orthopaedic surgery.Results Presently, mixed reality is widely used in the care of patients requiring complex reconstruction of the craniomaxillofacial skeleton for pre- and intraoperative planning. For upper extremity amputees, there is evidence that VR may be efficacious in the treatment of phantom limb pain. Furthermore, VR has untapped potential as a cost-effective tool for microsurgical education and for training residents on techniques in surgical and nonsurgical aesthetic treatment. There is utility for mixed reality in breast reconstruction for preoperative planning, mapping perforators, and decreasing operative time. VR has well- documented applications in the planning of deep inferior epigastric perforator flaps by creating three-dimensional immersive simulations based on a patient's preoperative computed tomography angiogram.Conclusion The benefits of AR and VR are numerous for both patients and surgeons. VR has been shown to increase surgical precision and decrease operative time. Furthermore, it is effective for patient-specific rehearsal which uses the patient's exact anatomical data to rehearse the procedure before performing it on the actual patient. Taken together, AR/VR technology can improve patient outcomes, decrease operative times, and lower the burden of care on both patients and health care institutions.
Keywords: plastic surgery; augmented reality; virtual reality